Thermoplastic resin composition

By adjusting the carbon-carbon double bond content of the butadiene block in the block copolymer and combining appropriate softeners and antioxidants to form a thermoplastic resin composition, the problems of cushioning surface coating steps and insufficient material weather resistance in the prior art are solved, and a buffer component with high adhesion and weather resistance are achieved.

CN119923438APending Publication Date: 2025-05-02TAICA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480004126.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-07
Filing Date
2024-07-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Prior Art When a protective layer formed by a polyurethane coating agent is provided on the outermost surface of the buffer member, multiple steps are required, time and labor are required, and when using styrene-butadiene-styrene block copolymer (SBS) as the main component, it is prone to deterioration due to heat, light, ozone, etc., resulting in white turbidity or oil leakage on the surface, and insufficient weather resistance.

Method used

By adjusting the amount of carbon-carbon double bonds in the butadiene block in the block copolymer composed of styrene blocks and butadiene blocks to a range of 59.0 to 68.5 mass%, combined with appropriate softeners and antioxidants, a thermoplastic resin composition is formed to improve the adhesion of the buffer member, inhibit peeling caused by stress deformation, and enhance weather resistance.

Benefits of technology

It is achieved that the buffering member has excellent adhesion and weather resistance without the installation of polyurethane coating agent, reduces labor and cost of preparation and assembly, and improves the light, ozone and moisture and heat resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005325203800000211
    Figure BDA0005325203800000211
  • Figure BDA0005325203800000221
    Figure BDA0005325203800000221
  • Figure BDA0005325203800000231
    Figure BDA0005325203800000231
Patent Text Reader

Abstract

Provided is a thermoplastic resin composition capable of forming a buffer member which has excellent adhesiveness without providing a coating layer on the surface thereof, is capable of suppressing peeling due to stress deformation, and also has weather resistance. The thermoplastic resin composition contains a styrene-based thermoplastic elastomer (A) and a softening agent (B), and the styrene-based thermoplastic elastomer (A) contains at least one type of block copolymer comprising at least a styrene block and a butadiene block. The total content of butadiene that retains a carbon-carbon double bond of a butadiene block in the styrene-based thermoplastic elastomer (A) is 59.0-68.5 mass%, and the blending ratio of the styrene-based thermoplastic elastomer (A) and the softening agent (B) is B / (A + B) = greater than 0.410 and less than 0.600 in terms of mass ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermoplastic resin composition suitable for use as a cushioning component for shoes such as a sole or an insole. Background Art

[0002] When providing a cushioning effect to externally visible parts such as shoe soles or smartphone protective cases, bag handles or shoulder pads, a cushioning component with excellent design is used. For example, in the design of shoes in fields that require functionality, such as sports shoes, a cushioning component with excellent cushioning properties is assembled in a sole component formed of resin or the like. This cushioning component is required to be lightweight from the perspective of not hindering operability or the user's movements. In addition, since it is assembled into the sole component in a manner that can be visible from the outside to show its functionality to the user, it also requires high design properties such as transparent appearance. Therefore, various cushioning components composed of styrene-based thermoplastic elastomers with low specific gravity (lightweight) and transparency have been proposed.

[0003] For example, in the case where such a cushioning component is applied to shoes, the applicant's patent document 1 proposes a cushioning component for shoes that is light, transparent, soft and has excellent adhesiveness. The cushioning component for shoes is obtained by molding the following cushioning composition for shoes, wherein the cushioning composition for shoes contains at least a styrene-ethylene-butylene-styrene block copolymer (SEBS), an amine-modified styrene-ethylene-butylene-styrene block copolymer (amine-modified SEBS) and a styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS) and a softener in a predetermined mixing ratio, and the molecular weight, styrene content and mixing ratio of each block copolymer are set to a predetermined range.

[0004] In recent years, in order to further pursue the functionality and design of the cushioning components, the shapes of the cushioning components have become diversified, such as by making use of the lightness of the cushioning components, increasing the size of the cushioning components, or forming a design that is eye-catching from the outside. For example, in the design of high-performance shoes, Figure 1 and Figure 2 As shown in (a) of FIG. 1 , the cushioning member 10 is arranged and assembled so as to protrude toward the side surface of the sole member 20 .

[0005] In such shoe designs, more reliable adhesion is required to cope with complex stress deformations such as compression deformation and shear deformation. Therefore, in the shoe cushioning component proposed in the above-mentioned Patent Document 1, a protective layer formed of a polyurethane coating agent with excellent adhesion is formed on the outermost surface of the cushioning component in order to improve the adhesion with the sole component.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 5966110 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, when a protective layer formed of the above-mentioned polyurethane coating agent is provided on the outermost surface of the cushioning component, the following steps are required: applying a primer agent on the surface of the molded product of the cushioning composition, drying the primer agent to form a primer treatment layer, applying a photocurable polyurethane coating agent on the primer treatment layer, drying the polyurethane coating agent, and photocuring the polyurethane coating agent to form a protective layer; since a large number of steps are required, it takes time and labor.

[0011] In order to improve the adhesion of the cushioning component itself without providing a coating using a polyurethane coating agent or the like on the cushioning component, a scheme of using a styrene-butadiene-styrene block copolymer (SBS) instead of a styrene-ethylene-butylene-styrene block copolymer (SEBS) as the main component of the styrene-based thermoplastic elastomer constituting the cushioning component has been studied. However, since the carbon-carbon double bonds contained in the butadiene block constituting the SBS are highly reactive, they are easily degraded by heat, light, ozone, etc., and the surface of the cushioning component becomes cloudy due to the generation of fine cracks, and oil seepage occurs on the resin surface, etc., which causes problems in weather resistance.

[0012] The present invention has been made in view of the above-mentioned problems, and its object is to provide a thermoplastic resin composition that can form a cushioning component, wherein the cushioning component has excellent adhesion even without providing a coating layer that helps to improve adhesion on its surface, can suppress peeling caused by stress deformation, and also has weather resistance.

[0013] Problem Solving Methods

[0014] The inventors of the present application have found that when the main component of a styrene-based thermoplastic elastomer is a block copolymer composed of a styrene block and a butadiene block having a carbon-carbon double bond, by adjusting the amount of carbon-carbon double bonds contained in the butadiene block to a specific range, a cushioning component that can achieve both improved adhesion, suppression of peeling caused by stress deformation, and improved weather resistance can be obtained. Based on this finding, the present invention has been completed.

[0015] In order to solve the above-mentioned problems, the thermoplastic resin composition of the present invention is a thermoplastic resin composition containing a styrene-based thermoplastic elastomer (A) and a softener (B), wherein the styrene-based thermoplastic elastomer (A) contains one or more block copolymers composed of at least a styrene block and a butadiene block, the total content of butadiene retaining the carbon-carbon double bonds of the butadiene blocks in the styrene-based thermoplastic elastomer (A) is 59.0 to 68.5% by mass, and the mixing ratio of the styrene-based thermoplastic elastomer (A) to the softener (B) is B / (A+B)=greater than 0.410 and less than 0.600 in terms of mass ratio.

[0016] The thermoplastic resin composition of the present invention contains a styrene-based thermoplastic elastomer (A) and a softener (B), wherein the styrene-based thermoplastic elastomer (A) contains at least one block copolymer composed of a styrene block and a butadiene block, wherein the total content of butadiene retaining the carbon-carbon double bonds of the butadiene block in the styrene-based thermoplastic elastomer (A) is 59.0 to 68.5% by mass, and the mixing ratio of the styrene-based thermoplastic elastomer (A) and the softener (B) is B / (A+B)=greater than 0.410 and less than 0.600 in terms of mass ratio, thereby obtaining a thermoplastic resin composition for forming a buffer component, wherein the buffer component has excellent adhesion, suppresses peeling caused by stress deformation, and has excellent weather resistance. Therefore, when the buffer component is formed from the thermoplastic resin composition, the buffer component and the adhered component can be bonded without providing a coating layer formed by a polyurethane coating agent or the like, thereby reducing the labor and manufacturing cost involved in the preparation of the buffer component and its assembly. In addition, weather resistance in the present invention means that degradation due to ozone, light or heat (including moist heat) is unlikely to occur.

[0017] In addition, preferably, in the thermoplastic resin composition of the present invention, the total content of styrene blocks in the styrene thermoplastic elastomer (A) is 31.5 to 41.0% by mass. Thus, a suitable styrene block content in the styrene thermoplastic elastomer (A) of the present invention is selected. Thus, a thermoplastic resin composition for forming a buffer component can be obtained, the buffer component has excellent adhesion to other components, can take into account both the suppression of peeling caused by stress deformation and the improvement of weather resistance, and has excellent appearance transparency and cushioning properties.

[0018] In addition, preferably, in the thermoplastic resin composition of the present invention, the main component of the styrene-based thermoplastic elastomer (A) is a styrene-butadiene-styrene triblock copolymer (A1). Thus, as a constituent component of the styrene-based thermoplastic elastomer (A) of the present invention, a suitable component is selected. By selecting the styrene-butadiene-styrene triblock copolymer (A1), a thermoplastic resin composition that can form a buffer component with excellent adhesion and excellent effect of suppressing peeling caused by stress deformation can be obtained.

[0019] In addition, preferably, in the thermoplastic resin composition of the present invention, the styrene-based thermoplastic elastomer (A) contains a styrene-butadiene-styrene triblock copolymer (A1) and a styrene-butadiene diblock copolymer (A2), and the mixing ratio of the styrene-butadiene-styrene triblock copolymer (A1) and the styrene-butadiene diblock copolymer (A2) is (A1): (A2) = 1: greater than 0 and less than 0.3 in terms of mass ratio. By constituting the styrene-based thermoplastic elastomer (A) with the styrene-butadiene-styrene triblock copolymer (A1) and the styrene-butadiene diblock copolymer (A2), the total content of butadiene retaining the carbon-carbon double bonds of the butadiene blocks in the styrene-based thermoplastic elastomer (A) can be easily adjusted to a specific range, and the melt fluidity of the thermoplastic resin composition of the present invention can be adjusted to a range that is easy to handle.

[0020] In addition, the above-mentioned styrene-butadiene-styrene triblock copolymer (A1) constituting the styrene-based thermoplastic elastomer (A) preferably contains a combination of a non-hydrogenated styrene-butadiene-styrene triblock copolymer and a partially hydrogenated styrene-butadiene-styrene triblock copolymer. By using a non-hydrogenated product and a partially hydrogenated product of a styrene-butadiene-styrene triblock copolymer in combination, it is easy to adjust the total content of butadiene that retains the carbon-carbon double bonds of the butadiene block in the styrene-based thermoplastic elastomer (A) to a specific range, thereby selecting a suitable block copolymer constituting the styrene-based thermoplastic elastomer (A) of the present invention.

[0021] In addition, preferably, in the thermoplastic resin composition of the present invention, the butadiene blocks in one or more block copolymers are substantially not hydrogenated. Thus, the total content of the butadiene blocks in the styrene-based thermoplastic elastomer (A) is the same as the total content of butadiene maintaining the carbon-carbon double bonds of the butadiene blocks. Therefore, in order to easily adjust the total content of the styrene block to an appropriate range while adjusting the amount of the carbon-carbon double bonds contained in the butadiene block to a specific range, the appropriate block copolymer constituting the styrene-based thermoplastic elastomer (A) of the present invention is selected. Moreover, in the thermoplastic resin composition involved in the present invention, even if the butadiene block is not hydrogenated, it has sufficient weather resistance by adjusting the amount of the carbon-carbon double bonds contained in the butadiene block to a specific range.

[0022] In the thermoplastic resin composition of the present invention, the softener (B) is preferably a paraffin oil or a naphthenic oil having a molecular weight of 300 to 1200. This can provide a thermoplastic resin composition capable of forming a cushioning member having excellent flexibility.

[0023] In addition, the thermoplastic resin composition of the present invention preferably further contains an antioxidant. This can provide a thermoplastic resin composition for forming a cushioning member having further improved weather resistance such as moist heat resistance.

[0024] In addition, the thermoplastic resin composition of the present invention preferably further contains a light stabilizer. This can provide a thermoplastic resin composition for forming a cushioning member having further improved weather resistance such as light resistance.

[0025] In addition, preferably, the hardness of the molded article of the thermoplastic resin composition of the present invention is ASKER C30 to 50 (SRIS 0101 standard, 23±2°C), and the haze value (JIS K 7136:2000 standard) is 15% or less. The molded article of the thermoplastic resin composition having such physical properties is excellent in flexibility and transparency, and is therefore suitable for use as a cushioning component applied to an externally visible area.

[0026] In addition, the cushioning component of the present invention is composed of a molded body of the above-mentioned thermoplastic resin composition. In addition, preferably, the cushioning component of the present invention is for shoes. Such a thermoplastic resin composition has excellent light resistance and design properties and is suitable for use as a cushioning component for shoes.

[0027] In addition, preferably, the thermoplastic resin composition of the present invention is a composition for 3D printer. The thermoplastic resin composition of the present invention is suitable for use as a composition for 3D printer having adhesiveness and transparency. Therefore, a cushioning component composed of a molded body of the thermoplastic resin composition of the present invention can be formed by molding with a 3D printer.

[0028] Effects of the Invention

[0029] According to the present invention, a thermoplastic resin composition and a cushioning member having the following excellent effects can be provided.

[0030] (1) A thermoplastic resin composition capable of forming a cushioning member having excellent adhesiveness, suppressing peeling due to stress deformation, and having weather resistance can be obtained.

[0031] (2) Even if a coating that helps improve adhesion is not provided on the surface of the buffer component, adhesion can be performed with sufficient strength, so that a coating step after the buffer component is formed is not required, which can shorten the operation time required for manufacturing and reduce manufacturing costs. In addition, since no coating is provided, the thermoplastic resin composition can be easily recycled, and sustainability is also improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1The figure schematically shows a sports shoe in which a cushioning member is assembled to a side surface of a sole member.

[0033] Figure 2 (a) and Figure 2 (b) are a partial cross-sectional view schematically showing the configuration of a conventional cushioning component and a sole portion, and a view showing a state when a load is applied, respectively.

[0034] Figure 3 (a) and Figure 3 (b) are a top view and a front view schematically showing the structure of the test piece prepared for the creep test and the peel strength measurement test in the example and the comparative example, respectively.

[0035] Figure 4 Instructions for use Figure 3 Figure 2. Method of creep testing of test pieces.

[0036] Figure 5 Instructions for use Figure 3 FIG. 1 is a diagram of a method for measuring the peel strength of a test piece.

[0037] Figure 6 It is a figure explaining the method of ozone exposure test for evaluating ozone resistance. DETAILED DESCRIPTION

[0038] The thermoplastic resin composition of the present invention comprises a styrene-based thermoplastic elastomer (A) and a softener (B), wherein the styrene-based thermoplastic elastomer (A) comprises one or more block copolymers composed of at least a styrene block and a butadiene block, and the total content of butadiene retaining the carbon-carbon double bonds of the butadiene blocks in the styrene-based thermoplastic elastomer (A) is 59.0 to 68.5% by mass. In addition, the mixing ratio of the styrene-based thermoplastic elastomer (A) to the softener (B) is B / (A+B)=greater than 0.410 and less than 0.600 in terms of mass ratio.

[0039] First, the styrene-based thermoplastic elastomer (A) constituting the thermoplastic resin composition is described. The styrene-based thermoplastic elastomer (A) involved in the present invention contains one or more block copolymers consisting of at least a styrene block and a butadiene block. As a block copolymer consisting of at least a styrene block and a butadiene block, a diblock copolymer of styrene-butadiene (hereinafter also referred to as SB), a triblock copolymer of styrene-butadiene-styrene (hereinafter also referred to as SBS), a tetrablock copolymer of styrene-butadiene-styrene-butadiene, etc. can be cited. Among them, from the viewpoint of the effect of the present invention, as the styrene-based thermoplastic elastomer (A), a triblock copolymer (SBS) of styrene-butadiene-styrene or a diblock copolymer (SB) of styrene-butadiene and a combination thereof can be preferably used. The triblock copolymer of styrene-butadiene-styrene that can be used in the present invention can be one compound or multiple compounds. Similarly, the diblock copolymer of styrene-butadiene can be one compound or multiple compounds. In addition, as the main component of styrene-based thermoplastic elastomer (A), it is preferred to use a triblock copolymer (SBS) of styrene-butadiene-styrene. In addition, in this specification, the main component refers to the component or component group that is most matched in the component or component group constituting the styrene-based thermoplastic elastomer (A). In order to maintain the carbon-carbon double bonds of the butadiene block, the block copolymer that can be used in the present invention is preferably substantially free of hydrogenation, but as long as the total content of butadiene that can maintain the carbon-carbon double bonds of the butadiene block is within the predetermined range described later, it can also be a partially hydrogenated block copolymer. As a partially hydrogenated block copolymer, specifically, for example, a triblock copolymer (SBBS) of styrene-butadiene-butylene-styrene can be cited, which is a partially hydrogenated product of a triblock copolymer (SBS) of styrene-butadiene-styrene. When a styrene-butadiene-styrene triblock copolymer (SBS) is used as the main component of the styrene-based thermoplastic elastomer (A) of the present invention, non-hydrogenated SBS that is substantially not hydrogenated and partially hydrogenated SBS (ie, SBBS) may be used in combination.

[0040] In the present invention, it is important that the total content of butadiene maintaining the carbon-carbon double bonds of the butadiene block in the block copolymer constituting the styrene-based thermoplastic elastomer (A) is adjusted to a range of 59.0 to 68.5% by mass. That is, due to the high reactivity of the carbon-carbon double bonds of the butadiene block, it becomes the cause of deterioration by reaction with ozone, light, and heat, and due to the high reactivity, the adhesion is improved, and the peeling caused by stress deformation is also suppressed. In the present invention, by adjusting the total content of butadiene maintaining the carbon-carbon double bonds of the butadiene block to a range of 59.0 to 68.5% by mass, a thermoplastic resin composition forming a buffer member can be obtained, the buffer member has excellent adhesion, can also suppress the peeling caused by stress deformation, and can withstand the weather resistance of ozone, light, heat, etc. is also excellent. In addition, in this specification, in the case where the block copolymer is substantially not hydrogenated, the content of butadiene maintaining the carbon-carbon double bonds of the butadiene block refers to the content of the butadiene block. When the block copolymer is partially hydrogenated, the content of the butadiene block is determined by multiplying the content by the ratio of the portion not hydrogenated.

[0041] In the present invention, from the viewpoint of improving adhesion, suppressing peeling caused by stress deformation, and improving weather resistance, the total content of butadiene maintaining the carbon-carbon double bonds of the butadiene block in the block copolymer constituting the styrene-based thermoplastic elastomer (A) is preferably in the range of 59.0 to 68.5% by mass, more preferably in the range of 62.0 to 68.0% by mass, and further preferably in the range of 64.0 to 66.0% by mass. Here, the total content of butadiene maintaining the carbon-carbon double bonds of the butadiene block is determined based on JIS K 6239-1:2017 Microstructure determination method (quantitative) of raw material rubber solution polymerization SBR-Part 1: 1 H-NMR and IR (cast film) 1 The value obtained by the H-NMR method (absolute method).

[0042] On the other hand, in the block copolymer constituting the styrene-based thermoplastic elastomer (A), the total content of the styrene block is preferably in the range of 31.5 to 41.0% by mass, more preferably in the range of 32.0 to 38.0% by mass, and further preferably in the range of 34.0 to 36.0% by mass. Thus, a thermoplastic resin composition forming a buffer component can be obtained, and the buffer component has excellent adhesion to other components, and can take into account the suppression of peeling caused by stress deformation and the improvement of weather resistance, and the appearance transparency and cushioning are also excellent. Here, the total content of the styrene block is based on the microstructure method (quantitative) of the raw rubber solution polymerization SBR based on JIS K6239-1:2017-Part 1: 1 H-NMR and IR (cast film) 1 The value obtained by the H-NMR method (absolute method).

[0043] As one embodiment of the present invention, a styrene-based thermoplastic elastomer (A) is formed by combining a triblock copolymer (A1) of styrene-butadiene-styrene and a diblock copolymer (A2) of styrene-butadiene, and it is easy to adjust the total content of butadiene that maintains the carbon-carbon double bonds of the butadiene block to a specific range. In addition, the melt fluidity of the thermoplastic resin composition of the present invention can also be adjusted to a range that is easy to handle. In addition, in the triblock copolymer (A1) of styrene-butadiene-styrene, in addition to the styrene-butadiene-styrene triblock copolymer that is substantially not hydrogenated (non-hydrogenated), a combination of a non-hydrogenated styrene-butadiene-styrene triblock copolymer and a partially hydrogenated styrene-butadiene-styrene triblock copolymer (so-called SBBS) is also included. From the viewpoint of the effects of the present invention, the mixing ratio of the styrene-butadiene-styrene triblock copolymer (A1) and the styrene-butadiene diblock copolymer (A2) is preferably (A1):(A2)=1:greater than 0 and less than 0.3, more preferably (A1):(A2)=1:0.03 or more and 0.2 or less in terms of mass ratio.

[0044] In addition, the molecular weight of the block copolymer constituting the styrene-based thermoplastic elastomer (A) is not particularly limited. As an example, the average molecular weight of the block copolymer can be 100,000 to 400,000, but from the viewpoint of mechanical strength, it is preferably 104,000 or more, and from the viewpoint of fluidity during adhesion and molding, it is preferably 360,000 or less. That is, the average molecular weight of the block copolymer is preferably 105,000 to 350,000. By setting the average molecular weight of the block copolymer to this range, excellent adhesion can be obtained, and a molded body in which peeling caused by stress deformation such as flow deformation is difficult to occur can be formed, and good fluidity can be obtained even during molding. It should be noted that the molecular weight in the present invention refers to the weight-average molecular weight Mw, which is the value measured by gel permeation chromatography (GPC) method.

[0045] The block copolymer constituting the styrene-based thermoplastic elastomer (A) in the present invention is not particularly limited, and as an example, KRATON (registered trademark) D1155, DX408 or DX405 (SBS; all products of Kraton Polymer Japan Co., Ltd.), KRATON (registered trademark) D1101, D1118 or DX423 (a mixture of SBS and SB; all products of Kraton Polymer Japan Co., Ltd.), etc. can be used.

[0046] In the block copolymer constituting the styrene-based thermoplastic elastomer (A) of the present invention, the total content of butadiene maintaining the carbon-carbon double bonds of the butadiene block is adjusted to a predetermined range, within which, in addition to the triblock copolymer (A1) of styrene-butadiene-styrene and the diblock copolymer (A2) of styrene-butadiene, other styrene-based block copolymers may also be contained. Other styrene-based block copolymers are not particularly limited, and as an example, styrene-ethylene butylene-styrene triblock copolymer (SEBS), styrene-isoprene-styrene triblock copolymer (SIS), styrene-ethylene propylene-styrene triblock copolymer (SEPS), styrene-isobutylene-styrene triblock copolymer (SIBS), styrene-ethylene / ethylene propylene-styrene block copolymer (SEEPS), styrene-ethylene propylene diblock copolymer (SEP), etc. may be cited.

[0047] Next, the softener (B) constituting the thermoplastic resin composition is described. The softener (B) is added mainly for the purpose of imparting flexibility to the composition. Regarding the mixing ratio of the softener (B), from the viewpoint of achieving the effect of the present invention while improving flexibility, the mixing ratio of the softener (B) relative to the sum of the styrene-type thermoplastic elastomer (A) and the softener (B) is preferably greater than 0.410 and less than 0.600 in terms of weight ratio, more preferably greater than 0.416 and less than 0.550, and particularly preferably greater than 0.420 and less than 0.500. By setting the mixing ratio of the softener (B) to the above range, a thermoplastic resin composition can be obtained that imparts flexibility to the styrene-type thermoplastic elastomer (A) while forming a buffer component with excellent adhesion, suppressed peeling caused by stress deformation, and excellent weather resistance.

[0048] As the softener in the present invention, for example, process oils such as paraffin oil, naphthenic oil or aromatic oil, synthetic resin softeners such as liquid polybutene or low molecular weight polybutadiene, rosin, etc. can be used. Among them, paraffin oil is preferably used as the process oil from the viewpoint of appearance transparency, and paraffin oil or naphthenic oil having a weight average molecular weight of 300 to 1200 is particularly preferably used from the viewpoint of excellent adhesion and mechanical strength. In addition, the softener can be used alone or in combination of a plurality of softeners having different physical properties such as composition or viscosity (molecular weight).

[0049] From the viewpoint of further improving weather resistance, the thermoplastic resin composition of the present invention may further contain an antioxidant. By containing an antioxidant, oxidation of the thermoplastic resin composition and its molded body (buffer component) can be prevented, thereby increasing the function of further improving weather resistance. Examples of the antioxidant include hindered amine antioxidants that function as chain terminators, hindered phenol antioxidants, phosphite antioxidants that function as peroxide decomposers, and thioether antioxidants. As the hindered amine antioxidant, a known substance can be appropriately selected, for example, N,N',N",N"'-tetrakis-(4,6-bis(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)-triazine-2-yl)-4,7-diazadecane-1,10-diamine, dibutylamine / 1,3,5-triazine / N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl-1,6-hexamethylenediamine / N-(2,2,6, 6-tetramethyl-4-piperidinyl)butylamine, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}], polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol, [bis(2,2,6,6-tetramethyl-1( 1,2,2,6,6-pentamethyl-4-piperidinyl) [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6 ,6-pentamethyl-4-piperidinyl) sebacate, 1-[2-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl]-4-〔3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy〕-2,2,6,6-tetramethylpiperidine, 4-benzoyloxy-2,2,6,6-tetramethylpiperidine, 8-acetyl-3-dodecyl-7,7,9,9-tetramethyl-1,3,8-triazaspiro[4.5]decane-2,4-dione, etc.

[0050] As the hindered phenol antioxidant, a known antioxidant can be appropriately selected, and examples thereof include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphate, 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a" -(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, ethylenebis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-t-phenylpentyl)ethyl]-4,6-di-t-phenylpentyl acrylate, etc.

[0051] As the phosphite antioxidant, a known antioxidant can be appropriately selected, for example, triphenylphosphite, tris(nonylphenyl)phosphite, dilauryl hydrogen phosphite, triethylphosphite, tridecylalkylphosphite, tris(2-ethylhexyl)phosphite, tris(tridecyl)phosphite, tristearylphosphite, diphenylmonodecylphosphite, monophenyldidecylphosphite, diphenylmono(tridecyl)phosphite, tetraphenyldipropylene glycol diphosphite, tetraphenyltetra(tridecyl)pentaerythritol tetraphosphite, hydrogenated bisphenol A phenol phosphite polymer, diphenyl hydrogen phosphite, 4,4'-butylene-bis(3-methyl-6-tert-butyl)phosphite, phenyl di(tridecyl)phosphite)tetra(tridecyl) 4,4'-isopropylidene diphenyl diphosphite, bis(tridecyl) pentaerythritol diphosphite, bis(nonylphenyl) pentaerythritol diphosphite, dilauryl pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, tris(4-tert-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, hydrogenated bisphenol A pentaerythritol phosphite polymer, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)octylphosphite, bis(2,4-dicumylphenyl) pentaerythritol diphosphite, etc.

[0052] As the thioether antioxidant, a known substance can be appropriately selected, and examples thereof include pentaerythritol tetrakis(3-dodecylthiopropionate), didodecylthiodipropionate, ditridecylthiodipropionate, ditetradecylthiodipropionate, dioctadecylthiodipropionate, 2-mercaptobenzimidazole, and 2,4-bis[(dodecylthio)methyl]-6-methylphenol.

[0053] For antioxidants, the antioxidants exemplified above can be used alone or in combination of two or more. In the case of combining two or more, the same component category can be combined, or different component categories can be combined. As a combination of different components, hindered phenol antioxidants, phosphite antioxidants, and thioether antioxidants are preferred. More specifically, more preferably, the phosphite antioxidant is 2,2'-methylenebis(4,6-di-tert-butylphenyl)octylphosphite, the hindered phenol antioxidant is 2-[1-(2-hydroxy-3,5-di-t-phenylpentyl)ethyl]-4,6-di-t-phenylpentyl acrylate, and the thioether antioxidant is 2,4-bis[(dodecylthio)methyl]-6-methylphenol. The addition ratio of the antioxidant is preferably 0.1 to 2 parts by mass relative to 100 parts by mass of the styrene thermoplastic elastomer (A), and more preferably 0.5 to 1.5 parts by mass. When a plurality of antioxidants are used in combination, it is also preferred that the total addition ratio of the antioxidants be within the above-mentioned range, and the addition ratio of each antioxidant be set within the range.

[0054] In addition, from the viewpoint of further improving weather resistance, the thermoplastic resin composition of the present invention may also contain a light stabilizer. By containing a light stabilizer, the photo-oxidative degradation of the thermoplastic resin composition and its molded body (buffer component) can be prevented, and the function of further improving weather resistance can be added. As light stabilizers, hindered amine light stabilizers (HALS) that have the function of capturing free radicals generated by light degradation and making them harmless, and benzotriazole ultraviolet absorbers that suppress the light-induced reaction that causes light degradation of polymers by absorbing ultraviolet rays and function as light resistance stabilizers can be cited, and can be used alone or in combination. As a hindered amine light stabilizer, in order to improve the storage stability of the composition, it is preferred to use a tertiary amine-containing hindered amine light stabilizer. Examples of tertiary amine-containing hindered amine light stabilizers include TINUVIN 622LD, TINUVIN 144, TINUVIN 765, CHIMASSOR C119FL (all manufactured by BASF), MARK LA-57, LA-62, LA-67, LA-63 (all manufactured by Asahi Denka Kogyo Co., Ltd.), SANOL LS-765, LS-292, LS-2626, LS-1114, LS-744 (all manufactured by Sankyo Co., Ltd.), etc. In addition, examples of ultraviolet absorbers include ultraviolet absorbers such as benzotriazoles, triazines, benzophenones, or benzoate compounds. As the ultraviolet absorber, a known ultraviolet absorber can be appropriately selected, and examples thereof include 2,4-di-tert-butyl-6-(5-chlorobenzotriazol-2-yl)phenol, 2-(2H-benzotriazol-2-yl)-4,6-di-tert-amylphenol, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol, a reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300, 2-(2H-benzotriazol-2-yl)-4,6-di-tert-amylphenol, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol, The present invention relates to benzotriazole type ultraviolet light absorbers such as benzotriazole-2-yl)-6-(straight chain and side chain dodecyl)-4-methylphenol, triazine type ultraviolet light absorbers such as 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol, benzophenone type ultraviolet light absorbers such as 2-hydroxy-4-n-octyloxybenzophenone (octabenzone), benzoate type ultraviolet light absorbers having free radical scavenging function such as 2,4-di-tert-butylphenyl-3,5-di-tert-butyl-4-hydroxybenzoate, etc. The above-mentioned hindered amine light stabilizer and ultraviolet light absorber may be one kind or two or more kinds. When the hindered amine light stabilizer and the ultraviolet light absorber are used in combination, the combination of the hindered amine light stabilizer and the benzophenone type ultraviolet light absorber is preferred.The light stabilizer is preferably added in an amount of 0.1 to 1.0 parts by mass, more preferably 0.3 to 0.7 parts by mass, relative to 100 parts by mass of the styrene-based thermoplastic elastomer (A). When the hindered amine light stabilizer and the ultraviolet absorber are used in combination, they may be combined in an appropriate ratio within the above range.

[0055] In addition, as an embodiment of the present invention, the thermoplastic resin composition may further contain other additives within the scope of not damaging the effects of the present invention. As additives, pigments or colorants, fillers, lubricants, release agents, etc. may be cited. These may be used alone or in combination.

[0056] The thermoplastic resin composition of the present invention is required to have flexibility to fully exert the cushioning effect. Specifically, the hardness of the molded body (SRIS 0101 standard, 23±2°C) is preferably ASKER C15 to 70, more preferably ASKER C25 to 60, and particularly preferably ASKER C30 to 50. Thus, a thermoplastic resin composition for forming a cushioning component can be obtained, wherein the cushioning component has sufficient flexibility to contribute to cushioning properties, excellent adhesion, is not easily peeled off due to stress deformation such as flow deformation, and has weather resistance.

[0057] In addition, from the viewpoint of improving designability, the thermoplastic resin composition of the present invention is required to have transparency, and specifically, the haze value (according to JIS K7136:2000) is preferably 40% or less, more preferably 30% or less, and particularly preferably 15% or less. Thus, a thermoplastic resin composition for forming a cushioning member can be obtained, the cushioning member having high appearance transparency, excellent adhesion, and being less likely to peel off due to stress deformation such as flow deformation, and also having weather resistance.

[0058] The thermoplastic resin composition of the present embodiment is manufactured by a known method for manufacturing a resin composition. Specifically, as an example, by using a melt kneader such as a single screw extruder, a twin screw extruder, a kneader, a Banbury mixer or a heating roller, a predetermined ratio is added with a styrene thermoplastic elastomer (A) and a softener (B) or a styrene thermoplastic elastomer (A), a softener (B), an antioxidant and / or a light stabilizer, and other various components added as required, the components are heated, and each component is uniformly kneaded in a molten state to obtain. In addition, in order to improve the dispersibility of the styrene thermoplastic elastomer (A) and the softener (B), it is also possible to melt-knead after the styrene thermoplastic elastomer (A) is allowed to absorb at least a portion of the softener (B) in advance.

[0059] After the thermoplastic resin composition obtained as described above is pelletized or filamentized as needed, it can be molded into a predetermined shape by known methods such as injection molding, extrusion molding, hollow molding, compression molding, calendering molding, or 3D modeling using a 3D printer, and a molded body of the thermoplastic resin composition of the present invention can be obtained. The haze value (according to JIS K7136:2000) of the molded body of the thermoplastic resin composition of the present embodiment is particularly preferably 15% or less. In addition, as hardness, ASKER C (SRIS 0101 standard) 30 to 50 is particularly preferred. Therefore, a molded body composed of a thermoplastic resin composition having high appearance transparency and sufficient softness that contributes to cushioning can be obtained, which is suitable for use as a cushioning component.

[0060] The cushioning component formed of a molded article of the thermoplastic resin composition of the present invention will be described. Figure 1 As shown, the cushioning component of one embodiment of the present invention can be suitably used as a cushioning component 10 for shoes such as sports shoes. The cushioning component 10 for shoes of this embodiment can be easily bonded to the sole component 20 such as EVA resin (ethylene-vinyl acetate copolymer resin) forming the sole of the shoe 1 by using an adhesive directly or via a primer treatment layer, and it is not necessary to set a coating using a polyurethane coating agent or the like during bonding. That is, since the cushioning component 10 for shoes itself has high adhesiveness, it can be firmly bonded to the sole component 20 by a known adhesive, and it is also difficult to produce peeling caused by flow deformation (creep). Therefore, according to the cushioning component 10 for shoes of the present invention, the manufacturing cost of shoes can be reduced, and a sturdy shoe can be obtained. And, as mentioned above, in addition to having weather resistance that is difficult to produce degradation caused by light, ozone, heat, etc., the cushioning component 10 for shoes is also excellent in appearance transparency (design) and cushioning.

[0061] In addition, the cushioning component formed by the molded body of the thermoplastic resin composition of the present invention is bonded to the adhered part according to the purpose by an adhesive. The adhesive can be appropriately selected from known adhesives compatible with styrene elastomers according to the material of the adhered part. For example, in footwear applications, adhesives for shoemaking such as polyurethane adhesives or chloroprene rubber adhesives can be applied. In addition, in order to improve the adhesion between the cushioning component and the adhered parts such as the sole component, and to make the bonding reliability more reliable, it is preferred that the cushioning component is bonded to the adhered part via a primer treatment layer. Here, the so-called primer treatment layer refers to a layer formed by treating the surface of the molded body (cushioning component) of the adhered part or the thermoplastic resin composition with a primer such as a surface treatment agent in advance. Thus, a higher bonding reliability with the adhered part can be achieved by the primer treatment layer. As a primer, for example, when the adhered part is a polyurethane rubber, it is preferred to use an acrylic primer or a chlorine primer. As the chlorine-based primer, for example, a composition in which chlorinated isocyanuric acid is dissolved in a solvent can be used. From the viewpoint of coating workability and adhesion, the concentration of chlorinated isocyanuric acid is preferably 0.5 to 5% by weight. As the chlorinated isocyanuric acid, chlorinated isocyanuric acid and its salts can be used, for example, trichloroisocyanuric acid, dichloroisocyanuric acid, sodium dichloroisocyanurate and its hydrate, potassium dichloroisocyanurate, calcium dichloroisocyanurate, magnesium dichloroisocyanurate, etc. can be mentioned.

[0062] In another embodiment, a cushioning member formed of a molded article of the thermoplastic resin composition of the present invention can be used in sports equipment or bags, automotive cushioning members, building material parts, etc., directly or by bonding with an adhesive through a primer treatment layer.

[0063] In addition, in order to further improve ozone resistance, the cushioning component composed of the molded body of the thermoplastic resin composition of the present invention may form a wax layer or a surface coating on the surface portion of the molded body (cushioning component) exposed to the atmosphere and light, or may be subjected to a surface treatment in which an energy ray reaching a predetermined depth region near the surface of the surface portion is irradiated to form a surface layer.

[0064] The wax layer for improving ozone resistance can be formed by coating the wax component on the surface of the molded body (buffer component). As the wax component, for example, petroleum wax, natural wax, etc. can be cited. In addition, synthetic wax obtained by refining or chemically treating a variety of waxes can also be used. These waxes can be used alone or in combination of two or more. As petroleum wax, paraffin wax, microcrystalline wax, etc. can be cited, preferably as a mixture of hydrocarbons with a carbon number of about 20 to 80, and more preferably paraffin wax. As natural wax, as long as it is a wax from a resource source other than petroleum, there is no particular limitation, for example, plant waxes such as candelilla wax, carnauba wax, wood wax, rice wax and jojoba wax, animal waxes such as beeswax, lanolin and spermaceti, mineral waxes such as ozokerite, ceresin and petrolatum, and their refined products, etc. can be cited. In addition, within the range that does not hinder the adhesiveness of the molded body (cushion component) of the thermoplastic resin composition, a wax component may be added to the thermoplastic resin composition, and a thin wax film may be attached to the surface of the molded body (cushion component) by oozing out little by little. From the viewpoint of the balance between ozone resistance and adhesiveness, the amount of wax added to the thermoplastic resin composition is preferably in the range of 0.1 to 5 parts by weight relative to 100 parts by weight of the thermoplastic resin composition.

[0065] In addition, the surface coating for improving ozone resistance can be formed by a known method such as applying an ozone-resistant resin composition to the surface of a molded body (cushion component). As the ozone-resistant resin composition, there is no particular limitation as long as it is a resin composition with excellent adhesion to the surface of a molded body of a thermoplastic resin composition, but when the surface of the molded body is visualized as a design, a resin composition with light transmittance is preferred.

[0066] In addition, in the case of surface treatment by energy ray irradiation for improving ozone resistance, the double bonds of the butadiene block in a predetermined depth region near the surface of the molded body of the thermoplastic resin composition are crosslinked with energy rays, and the content of the double bonds is reduced, thereby forming a surface treatment layer with excellent ozone resistance. As energy rays, radiation, electron beams, etc. can be applied. The irradiation conditions of the energy rays can be appropriately set according to the required ozone resistance.

[0067] The cushioning component formed by the molded body of the thermoplastic resin composition of the present invention may also have a decorative layer formed on its surface. In addition, when the above-mentioned surface coating or wax layer is formed, the decorative layer is formed between these surface coatings and the molded body. The decorative layer can be formed by known methods such as coating and printing using existing coatings or inks. The thermoplastic resin composition of the present invention has an effect of easily and beautifully forming a decorative layer because of its excellent adhesion to coatings or inks.

[0068] Example

[0069] The present invention will be described in detail below using examples. The evaluation methods for physical properties such as adhesion, weather resistance, and transparency of the thermoplastic resin compositions in the following examples and comparative examples are as follows.

[0070] (1) Adhesion 1: Creep test (flow deformation)

[0071] use Figure 3 and Figure 4 A specific creep test method will be described. Figure 3 The structure of the sample piece 50 is schematically shown. Figure 4 The creep test method of the test piece is shown in FIG. Figure 3 The test piece 50 shown. The molded bodies of the thermoplastic resin compositions in the examples and comparative examples were molded into strips (width 20 mm×length 60 mm×thickness 3 mm) to form test pieces 51. A polyurethane sheet 52 (Kuramiron U2195 manufactured by Kuraray Co., Ltd., width 20 mm×length 60 mm×thickness 3 mm) made into the same strip as the test piece 51 was bonded to the test piece 51 with an adhesive 53 to obtain the test piece 50. More specifically, the surface of the test piece 51 was wiped with a low-dust wiping paper (Kimwipe, registered trademark) soaked in ethanol, and the surface of the polyurethane sheet 52 was wiped with a low-dust wiping paper (Kimwipe, registered trademark) soaked in acetone, and then dried at 60°C for 5 minutes. An adhesive primer (a product of No-tape Industries, used after mixing and dissolving P-66 (thinner) : P-66 (granules) = 100:2) was applied to one side of the test piece 51, and dried at 60°C for 5 minutes. An adhesive prepared by mixing Adhesive 1 (a product of Daito Resin Co., Ltd., GE6602) and Adhesive 2 (a product of Daito Resin Co., Ltd., GE366S) in a ratio of Adhesive 1 : Adhesive 2 = 100:5 was applied thereon, and dried at 60°C for 5 minutes. This adhesive was applied thereon again, and dried at 60°C for 5 minutes. In addition, an adhesive prepared by mixing Adhesive 3 (812TF manufactured by Henkel) and Adhesive 4 (Desmodur RFE manufactured by Bayer) in a ratio of Adhesive 3 : Adhesive 4 = 100:5 was applied to one side of the polyurethane sheet 52, and dried at 60°C for 5 minutes. The adhesive was then applied thereon and dried at 60°C for 5 minutes. After the adhesive applied to the test piece 51 and the polyurethane sheet 52 was dried, the test piece 51 and the polyurethane sheet 52 were quickly attached. The test piece 51 was placed with the side facing upward and a hand roller was applied with a force of 2 to 3 kgf / cm 2 The test piece 50 is obtained by pressing the test piece 51 and the polyurethane sheet 52 with the adhesive 53. Figure 3As shown in (b), for one end in the longitudinal direction, the portion 15 mm from the end toward the other end in the longitudinal direction is regarded as the unbonded portion. The sample piece 50 is cured at 40°C for more than 2 hours and then used in the creep test. During the test, if there is adhesive accumulation at the end Q0 of the bonding portion of the sample piece 50, the apparent strength will increase. Therefore, Figure 3 The end Q0 of the adhesive portion of the sample piece 50 shown in (b) is cut with a cutter to form a 1 mm incision along the adhesive layer toward the adhesive portion side, and the test is performed after the incision is formed. Figure 4 As shown in (a), the polyurethane sheet 52 side of the test piece 50 is fixed horizontally on the fixture as the upper surface, and a 200g weight W is fixed to the end of the non-bonded part of the test piece 51 with a vinyl tape. Under the condition of applying a tensile load in the direction of gravity, it is placed in a hot air oven (manufactured by Tokyo Riko Machine Co., Ltd., model: WFO-520W) at 40°C for 24 hours. After 24 hours, as shown in FIG. Figure 4 As shown in (b), the distance from the position Q0 of the end of the bonding portion before the test to the position Q1 of the end of the bonding portion after the test where peeling occurs due to creep (the distance between Q0 and Q1) is measured.

[0072] In the adhesion evaluation of the creep test, when the measured value of the distance where peeling occurs (the length between Q0 and Q1) is 0 mm (no peeling), it is evaluated as excellent "○", when the measured value is less than 1 mm (slight peeling), it is evaluated as acceptable "△", and when the measured value exceeds 1 mm (peeling), it is evaluated as poor "×".

[0073] (2) Adhesion 2: Peel strength

[0074] The peel strength of each test piece was measured in accordance with JIS K6854-3. The test piece was made in the same manner as the test piece 50 in the creep test. The test piece 50 was cured at 40°C for more than 2 hours and then used in the peel strength test. During the test, if there is adhesive accumulation at the end Q0 of the bonding portion of the test piece 50, the apparent strength will increase. Therefore, as in the creep test, the test piece 50 was tested from the end Q0 of the bonding portion. Figure 3 The end Q0 of the adhesive portion of the sample piece 50 shown in (b) is cut with a cutter to form a 1 mm incision along the adhesive layer toward the adhesive portion side, and the test is performed after the incision is formed. Figure 5 (a) and Figure 5 As shown in (b), a tensile testing machine (Autograph (registered trademark), AT-100N, manufactured by Shimadzu Corporation) was used to peel off the test piece 51 and the polyurethane sheet 52 of the sample piece 50, and the peel strength was measured. Figure 5In the figure, 54 represents the fixed side tensile fixture, and 55 represents the movable side tensile fixture. The force sensor is 1kN (100kgf), the test speed is 50mm / min, and the initial gap between the fixed side tensile fixture 54 and the movable side tensile fixture 55 is 20mm. (It should be noted that Figure 5 (a) and Figure 5 In (b), the adhesive 53 constituting the sample piece 50 is omitted.

[0075] The peeling state (peeling mode) of the molded body interface in each test piece 51 after measuring the peel strength was evaluated as follows. An FT-IR device (PerkinElmer, infrared microscope system Spotlight 200) was used at 380 to 4000 cm -1 In the wave number range of , the stripping surface of the polyurethane sheet 52 side of each test piece 50 and the stripping surface of the test piece 51 side are analyzed respectively by total reflection measurement (ATR method). Through analysis, the situation that the spectrum of SBS as the constituent component of the molded body of each test piece 51 is not detected on the stripping surface of the test piece 51 side and the stripping surface of the polyurethane sheet 52 side is regarded as "interface stripping". On the other hand, in the case of not belonging to this "interface stripping", the situation that the spectrum of SBS is detected on the stripping surface of the test piece 51 side and the stripping surface of the polyurethane sheet 52 side, which is mainly the destruction in the molded body, is regarded as "molded body material rupture". Here, the spectrum of SBS refers to the spectrum obtained by measuring the surface of the molded body constituting each test piece 51 using FT-IR, and the spectrum obtained by measuring the stripping surface of the polyurethane sheet 52 side of the test piece 50 and the stripping surface of the test piece 51 side is compared with each characteristic absorption band of the spectrum of SBS to identify the material, thereby judging whether there is SBS. In addition, the identification method of the spectrum is based on JIS K 6230.

[0076] Regarding the evaluation of the adhesiveness of the peel strength, for the test piece in which material damage occurred inside the molded body, the measured value was 4kgf / 20mm or more and was evaluated as excellent "○", and the measured value was less than 4kgf / 20mm and was evaluated as poor "×". In addition, for the test piece in which interface peeling occurred, it was evaluated as poor "×" regardless of the value of the measured value.

[0077] (3) Ozone resistance

[0078] use Figure 6, the ozone exposure test method for evaluating ozone resistance is specifically described. The molded bodies of each thermoplastic resin composition in the examples and comparative examples are respectively molded into strips (width 20 mm×length 60 mm×thickness 3 mm) as test pieces 61. The test piece 61 is pasted on the curved surface 63 (radius 40 mm) of the semi-cylindrical fixing fixture 62, and a warping load is applied to the test piece 61. The fixing fixture 62 is fixed on the setting table 64 of the box-shaped test tank 60 in such a way that the distance from the test piece 61 to the ceiling of the test tank 60 is 210 mm. In the test tank 60, a water tank 65 filled with water 66 is arranged below the setting table 64. An inlet pipe 67 and an outlet pipe 68 are provided at the upper part of the test tank 60. Ozone gas generated by an ozone gas generator (manufactured by Eco Design, ED-OG-7TC) is introduced into the test tank 60 from the inlet pipe 67, and the gas in the test tank 60 is taken out from the outlet pipe 68. The ozone gas concentration contained in the gas in the test tank 60 is measured by an ozone gas concentration meter (manufactured by Eco Design, OZM-7000G2). The ozone exposure test is performed in the following manner: ozone gas is perfused into the test tank 60 so that the concentration of ozone gas in the test tank 60 is 0.5ppm, and a test piece 61 is placed in the test tank 60 for more than 16 hours, and an image of the appearance change of the test piece 61 during this period is photographed. The photographed image is confirmed, and the time when cracks caused by ozone exposure are observed on the test piece 61 is calculated. In addition, the ozone gas concentration of 0.5ppm in the test tank 60 in this test is equivalent to a concentration 100 times the ozone gas concentration in the atmosphere.

[0079] Regarding the evaluation of ozone resistance in the ozone exposure test, when the time for cracks due to ozone exposure to be observed in the test piece 61 exceeded 16 hours (16<) from the start of the test, it was evaluated as excellent "○", and when it was less than 16 hours, it was evaluated as poor "×".

[0080] (4)Lightfastness

[0081] Each thermoplastic resin composition having the structure shown in the examples and comparative examples was molded into a shape without a cut corner (dumbbell No. 3, thickness 3 mm) to prepare a test piece. Three test pieces were each held and hung in the chamber of a light resistance tester (Q-SUN Xe-3 xenon arc tester manufactured by Q-LAB) at a temperature of 40°C and an irradiation dose of 0.35 W / m 2 The test pieces were irradiated with xenon arc light (wavelength 340 nm) under the conditions of irradiation for 60 hours. The state of each test piece before and after the test was observed visually and by hand to confirm whether there was any discoloration such as yellowing and oil bleeding.

[0082] Regarding the evaluation of light resistance, when neither "yellowing or other discoloration" nor "bleeding" was observed in the test piece and there was no change in appearance before and after the test, it was judged as A; when only either "yellowing or other discoloration" or "bleeding" was observed in the test piece, it was judged as B; when both "yellowing or other discoloration" and "bleeding" were observed in the test piece, it was judged as C; when all the test pieces were judged as A, it was evaluated as excellent "◎", when no C-judged products were included but B-judged test pieces were included, it was evaluated as good "○", and when a C-judged test piece was included, it was evaluated as poor "×".

[0083] (5) Moisture and heat resistance

[0084] According to JIS K6252-1B method, each thermoplastic resin composition of the composition shown in the examples and comparative examples was molded into 10 test pieces of uncut angular shape (dumbbell B type), 5 of which were exposed to a hot and humid environment of 95% humidity and 80°C for 4 weeks, and the remaining 5 were stored in a room temperature environment for 4 weeks. After drying at 40°C for 1 day, the maximum load value F [N] at break at a tensile speed of 500 mm / min was measured using a tensile tester (Autograph (registered trademark), AT-100N manufactured by Shimadzu Corporation) and divided by the thickness t [m] of the test piece to calculate the tensile strength at break (MPa). The average of the two values ​​on both sides of the median of the tensile strength at break of the 5 test pieces was taken as the tensile strength at break (MPa).

[0085] In the evaluation of the moisture-heat resistance based on the tensile breaking strength, the degree of deterioration of the molded body of the thermoplastic resin composition during moisture-heat exposure is evaluated. First, the change rate of the tensile breaking strength caused by moisture-heat exposure is calculated according to the formula "change rate (%) = (the absolute value of the value obtained by subtracting the measured value of the tensile breaking strength of the test piece after moisture-heat storage from the measured value of the tensile breaking strength of the test piece after moisture-heat storage) / (the measured value of the tensile breaking strength of the test piece after moisture-heat storage)". When the change rate is less than 10%, it is evaluated as excellent "◎", when the change rate is greater than 10% and less than 20%, it is evaluated as good "○", and when the change rate is greater than 20%, it is evaluated as poor "×".

[0086] (6) Haze value (transparency)

[0087] According to JIS K 7136:2000, the haze of each test piece was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., spectrophotometer SH7000). As the test piece, the molded body of each thermoplastic resin composition in the embodiment and the comparative example was molded into a sheet (50 mm long × 50 mm wide × 3 mm thick). When the haze value is less than 15%, it is set as excellent "○", and when it is greater than 15%, it is set as poor "×". It should be noted that even if the haze value is less than 15%, it is also evaluated as poor "×" when bubbles are generated.

[0088] (7) Hardness (ASKER C)

[0089] The hardness of each test piece was measured using an ASKER C hardness meter (SRIS 0101 standard) in accordance with JIS K 6253. As the test piece, the molded body of each thermoplastic resin composition in the embodiment and the comparative example was molded into a molded body of 60 mm in length × 60 mm in width × 3 mm in thickness and 4 pieces were stacked in the thickness direction to form a layer thickness of 12 mm. When ASKER C is 30 to 50, it is judged as excellent "○", when it is 25 or more and less than 30 or greater than 50 and less than 60, it is judged as acceptable "△", and when it is less than 25 or greater than 60, it is judged as poor "×".

[0090] (8) MFR: melt mass flow rate (fluidity)

[0091] The melt mass flow rate of each thermoplastic resin composition was measured at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS K 7210-1B method.

[0092] In addition, the specifications of the constituent components of the thermoplastic resin compositions prepared in the following examples and comparative examples are shown in Tables 1 and 2. It should be noted that, among the constituent components, for components A11 to A13 and A21 to A23, the butadiene blocks in each block copolymer constituting the styrene-based thermoplastic elastomer (A) are not hydrogenated, and for component A14 (SBBS), the butadiene blocks in the block copolymer are partially hydrogenated. In addition, the molecular weight of the SBS of component A21 constituting the styrene-based thermoplastic elastomer (A) is an actual measured value. In addition, component A23 contains 31% of oil in addition to component (A) (SBS and SB). And, in the softener (B), the molecular weight of the cycloalkane of component B3 is an actual measured value.

[0093] In addition, the butadiene content and styrene content in each component of Table 1 were measured in accordance with JIS K6239-1:2017 Raw rubber - Method for determining the microstructure of solution-polymerized SBR (quantitative) - Part 1: 1H-NMR and IR (cast film) method (absolute method), using deuterated chloroform as the measurement solvent and under the condition of a measurement concentration of 10 mg / 0.7 mL. The measurement device used was a nuclear magnetic resonance spectrometer (NMR) device AVANCE NEO 700 manufactured by Bruker.

[0094] [Table 1]

[0095]

[0096] [Table 2]

[0097]

[0098] [Example 1]

[0099] The thermoplastic resin composition of this embodiment was prepared according to the following steps, and various physical properties and effects were evaluated by the above tests. The proportions of the constituents of the styrene-based thermoplastic elastomer (A) in this embodiment and the subsequent embodiments and comparative examples are shown in Table 3 below. Using the constituents shown in Table 1, as the styrene-based thermoplastic elastomer (A), 27 parts by mass of SBS (styrene-butylene-styrene triblock copolymer) (A11) with a butadiene block content of 60% by mass and 28 parts by mass of a mixture of SBS and SB (styrene-butadiene diblock copolymer) with a total butadiene block content of 70% by mass (A21) were weighed separately. Next, using the components shown in Table 2, 45 parts by weight of paraffin oil (B1) having a molecular weight of 400 as a softener (B), 0.63 parts by weight of a mixture of a sulfide antioxidant (C1), a hindered phenol antioxidant (C2) and a phosphite antioxidant (C3) at a weight ratio of C1:C2:C3=26.7:26.7:46.6 as an antioxidant (C), and 0.5 parts by weight of a mixture of a benzotriazole light stabilizer (D1) and a hindered amine light stabilizer (D2) at a weight ratio of D1:D2=1:1 as a light stabilizer (D) were prepared separately. After each block copolymer and paraffin oil were mixed at room temperature, the antioxidant (C) and the light stabilizer (D) were dry mixed by manual stirring, and the mixture was heated at 100°C for 12 hours to allow the paraffin oil to be absorbed and dispersed in the styrene thermoplastic elastomer (A). The mixture was kneaded for 15 minutes at 130 to 170° C. and 40 rpm using a batch type twin screw kneader (TD3-10MDX manufactured by Toshin Co., Ltd.) to obtain a thermoplastic resin composition of Example 1. The composition was injection molded at 170 to 190° C. or press molded at 130 to 150° C. to obtain a sheet molded body, which was cut into a predetermined test piece shape, to obtain a molded body of a predetermined test piece shape used in the above-mentioned various evaluation tests.

[0100] [Table 3]

[0101]

[0102] ※The values ​​in parentheses are the values ​​of component (A) after removing the oil component contained in A23.

[0103] The thermoplastic resin composition and its molded article were used to perform the above-mentioned various evaluation tests and evaluate various physical properties. The results of Example 1 are shown in Table 4.

[0104] [Examples 2 to 16]

[0105] In addition, the components and blending ratio of the styrene-based thermoplastic elastomer (A) were changed as shown in Table 3, and the components and blending ratio of the softener (B) and the blending ratio of the antioxidant (C) and the light stabilizer (D) were changed as shown in Tables 4 to 6 below, respectively. The same operation as in Example 1 was performed to obtain the thermoplastic resin composition of each example. In the same manner as in Example 1, the various evaluation tests described above were performed using the obtained thermoplastic resin composition and its molded body, and various physical properties were evaluated. The results of Examples 2 to 6 are shown in Table 4, the results of Examples 7 to 12 are shown in Table 5, and the results of Examples 13 to 16 are shown in Table 6. In addition, the results of the wet heat resistance test of the molded body of the thermoplastic resin composition obtained in Examples 9 and 10 are shown in Table 8.

[0106] [Comparative Examples 1 to 4]

[0107] In addition, the thermoplastic resin compositions of each example were obtained in the same manner as in Example 1 except that the constituent components and compounding ratio of the styrene-based thermoplastic elastomer (A) were changed as shown in Table 3, and the compounding ratios of the softener (B), the antioxidant (C), and the light stabilizer (D) were changed as shown in Table 7 below. The above-mentioned various evaluation tests were carried out using the obtained thermoplastic resin compositions and their molded articles in the same manner as in Example 1, and various physical properties were evaluated. The results of Comparative Examples 1 to 4 are shown in Table 7.

[0108] [Table 4]

[0109]

[0110] [Table 5]

[0111]

[0112] [Table 6]

[0113]

[0114] [Table 7]

[0115]

[0116] [Comparative Example 5]

[0117] In addition, the constituent components and the mixing ratio of the styrene-based thermoplastic elastomer (A) were changed as shown in Table 3, and the mixing ratios of the softener (B), the antioxidant (C) and the light stabilizer (D) were changed as shown in Table 8 below. Otherwise, the same operation as in Example 1 was performed to obtain the thermoplastic resin composition of Comparative Example 5. In addition, in A23 used as a constituent component of the styrene-based thermoplastic elastomer (A), 31% by mass of oil components were contained in addition to SBS and SB. Therefore, the total amount of the (A) component was calculated by removing the amount of the oil components. Using the molded body of the obtained thermoplastic resin composition, the moisture and heat resistance and light resistance tests were carried out to evaluate various physical properties. The results of Comparative Example 5 and the results of Examples 9 and 10 are shown in Table 8.

[0118] [Table 8]

[0119]

[0120] From the results of Examples 1 to 16 shown in Tables 4, 5 and 6 and Comparative Examples 1 to 5 shown in Tables 7 and 8, it can be seen that by adopting the structure of the present invention, a thermoplastic resin composition capable of forming a buffer component can be obtained, wherein the buffer component not only has excellent adhesion and excellent peel strength, but also can suppress peeling caused by flow deformation (creep) that reproduces severe stress deformation conditions, and has weather resistance.

[0121] Specifically, from the results of Examples 1 to 16, it can be seen that the thermoplastic resin composition having a total content of butadiene retaining the carbon-carbon double bonds of the butadiene blocks in the styrene-based thermoplastic elastomer (A) in the range of 62.0 to 67.9 mass % and a blending ratio of the styrene-based thermoplastic elastomer (A) to the softener (B) in the range of B / (A+B)=0.416 to 0.550 in terms of mass ratio has excellent peel strength accompanied by material failure of the molded body in a peel test, and also suppresses flow deformation in a creep test, and is excellent in adhesion to other parts, appearance transparency, flexibility, ozone resistance and light resistance. It is also found that the thermoplastic resin composition having a total content of styrene blocks in the styrene-based thermoplastic elastomer (A) of 31.9 to 38.0% by mass has excellent peel strength accompanied by material failure of the molded body in a peel test, and also suppresses flow deformation in a creep test, and is excellent in adhesion to other parts, appearance transparency, flexibility, ozone resistance, and light resistance.

[0122] In addition, it can be seen that for the thermoplastic resin compositions of Examples 1 to 16, if the mixing ratio of the styrene-butadiene-styrene triblock copolymer (A1) and the styrene-butadiene diblock copolymer (A2) is in the range of (A1): (A2) = 1: 0.00 to 0.20 by mass ratio, a cushioning component is obtained that has excellent peel strength accompanied by material failure of the molded body in a peel test, and also suppresses flow deformation in a creep test, and has excellent adhesion to other components, appearance transparency, flexibility, ozone resistance and light resistance. In addition, it can be seen that by setting the mass ratio to (A1): (A2) = 1: greater than 0 and up to 0.20, the melt flowability (MFR) of the thermoplastic resin composition can be adjusted to a range that is easy to handle. In addition, it can be confirmed that the softener (B) has flexibility suitable for a cushioning component and has good physical properties even if it is a paraffin oil with a molecular weight of 400 or 700 or a naphthenic oil with a molecular weight of 300.

[0123] In Examples 1 to 12, only a non-hydrogenated styrene-butadiene-styrene triblock copolymer that was not substantially hydrogenated was used as the styrene-butadiene-styrene triblock copolymer (A1), while in Examples 13 to 16, a partially hydrogenated styrene-butadiene-styrene triblock copolymer (i.e., SBBS) was used in combination with a non-hydrogenated styrene-butadiene-styrene triblock copolymer (non-hydrogenated SBS) as the styrene-butadiene-styrene triblock copolymer (A1). From these results, it can be seen that for the thermoplastic resin composition containing the styrene-butadiene-styrene triblock copolymer (A1) and the styrene-butadiene diblock copolymer (A2), even when a non-hydrogenated SBS and SBBS are used in combination as the styrene-butadiene-styrene triblock copolymer (A1), the same excellent effect as when only the non-hydrogenated SBS is used can be obtained. In addition, the thermoplastic resin compositions of Examples 13 to 16 had ozone resistance and light resistance and exhibited excellent weather resistance even though they did not contain any of an antioxidant and a light stabilizer.

[0124] Furthermore, by comparing the results of Comparative Example 1 and Example 6 in which the styrene-based thermoplastic elastomer (A) is composed of SBS, it can be seen that the thermoplastic resin composition having a total butadiene content of 58.5% by mass and a total styrene content of 41.5% by mass in the styrene-based thermoplastic elastomer (A) is poor in adhesiveness. On the other hand, it can be seen that the thermoplastic resin composition having a total butadiene content of 65.6% by mass and a total styrene content of 34.4% by mass in the styrene-based thermoplastic elastomer (A) is improved in adhesiveness.

[0125] In addition, by comparing the results of Comparative Example 2 and Example 8 in which the styrene-based thermoplastic elastomer (A) is composed of a combination of SBS and SB, it can be seen that the thermoplastic resin composition having a total butadiene content of 69.1% by mass and a total styrene content of 30.9% by mass in the styrene-based thermoplastic elastomer (A) is poor in ozone resistance. On the other hand, it can be seen that the thermoplastic resin composition having a total butadiene content of 65.0% by mass and a total styrene content of 35.0% by mass in the styrene-based thermoplastic elastomer (A) is improved in ozone resistance.

[0126] In addition, from the results of Comparative Example 3 and Example 4, it can be seen that the thermoplastic resin composition in which the mixing ratio of the styrene-based thermoplastic elastomer (A) and the softener (B) is B / (A+B)=0.410 by mass ratio has poor ozone resistance, and the thermoplastic resin composition in which B / (A+B)=0.416 has sufficient ozone resistance. From the results of Comparative Example 4 and Example 5, it can be seen that the thermoplastic resin composition in which the mixing ratio of the styrene-based thermoplastic elastomer (A) and the softener (B) is B / (A+B)=0.600 by mass ratio has poor adhesion, and the thermoplastic resin composition in which B / (A+B)=0.550 has improved adhesion.

[0127] Furthermore, from the results of Examples 8 to 10 and 13 to 16, it was confirmed that the thermoplastic resin composition of the present invention has ozone resistance, light resistance, and moist heat resistance and exhibits excellent weather resistance even without containing an antioxidant and / or a light stabilizer.

[0128] Furthermore, from the results of Comparative Example 5 and Example 10 shown in Table 8, it can be seen that the thermoplastic resin composition having a total butadiene content of 68.8% by mass in the styrene-based thermoplastic elastomer (A) has insufficient moisture heat resistance and light resistance, whereas the thermoplastic resin composition having a total butadiene content of 65.0% by mass in the styrene-based thermoplastic elastomer (A) has improved moisture heat resistance and light resistance.

[0129] The present invention is not limited to the above-described embodiments or examples, and various design modifications within the scope not departing from the gist of the invention described in the claims are also included in the technical scope.

[0130] Industrial availability

[0131] The thermoplastic resin composition of the present invention is mainly used for cushioning components for shoes such as soles and insoles, and is also widely used in the field of personal products such as bag handles and shoulder pads, shoes and bags, etc.

[0132] Reference numerals

[0133] 1 Shoes

[0134] 10.10a Shoe cushioning components

[0135] 11a Molded body

[0136] 12 Primer layer

[0137] 13 Protective coating

[0138] 20 Sole components

[0139] 21 Adhesion surface between cushioning components and sole components of shoes

[0140] 50 specimens

[0141] 51 Test piece (cushion member of the embodiment or comparative example)

[0142] 52 Polyurethane sheet

[0143] 53 Adhesive

[0144] 54 Fixed side tensile fixture

[0145] 55 Movable side tensile fixture

[0146] Q0 End of bonding part

[0147] Q1 End of the bonded part after the test

[0148] W Heavy Object

[0149] 60 Test Tanks

[0150] 61 Test piece (cushion member of the embodiment or comparative example)

[0151] 62 Fixing fixture

[0152] 63 Surface

[0153] 64 Setting Station

[0154] 65 sink

[0155] 66 Water

[0156] 67 Introduction tube

[0157] 68 discharge pipe

Claims

1. A thermoplastic resin composition comprising a styrene-based thermoplastic elastomer (A) and a softener (B), characterized in that: The styrene-based thermoplastic elastomer (A) contains one or more block copolymers consisting of at least a styrene block and a butadiene block. The total content of butadiene maintaining the carbon-carbon double bonds of the butadiene blocks in the styrene-based thermoplastic elastomer (A) is 59.0 to 68.5% by mass, The mixing ratio of the styrene-based thermoplastic elastomer (A) and the softener (B) is B / (A+B)=greater than 0.410 and less than 0.600 in terms of mass ratio.

2. The thermoplastic resin composition according to claim 1, characterized in that The total content of the styrene blocks in the styrene-based thermoplastic elastomer (A) is 31.5 to 41.0% by mass.

3. The thermoplastic resin composition according to claim 2, characterized in that The main component of the styrene-based thermoplastic elastomer (A) is a styrene-butadiene-styrene triblock copolymer (A1).

4. The thermoplastic resin composition according to claim 3, characterized in that The styrene-based thermoplastic elastomer (A) contains the styrene-butadiene-styrene triblock copolymer (A1) and the styrene-butadiene diblock copolymer (A2), The mixing ratio of the styrene-butadiene-styrene triblock copolymer (A1) and the styrene-butadiene diblock copolymer (A2) is (A1):(A2)=1:greater than 0 and less than 0.3 in terms of mass ratio.

5. The thermoplastic resin composition according to claim 3 or 4, characterized in that: The styrene-butadiene-styrene triblock copolymer (A1) contains a combination of a non-hydrogenated styrene-butadiene-styrene triblock copolymer and a partially hydrogenated styrene-butadiene-styrene triblock copolymer.

6. The thermoplastic resin composition according to any one of claims 1 to 4, characterized in that: The butadiene blocks in the one or more block copolymers are substantially not hydrogenated.

7. The thermoplastic resin composition according to any one of claims 1 to 4, characterized in that: The softener (B) is a paraffinic oil or a naphthenic oil having a molecular weight of 300 to 1200.

8. The thermoplastic resin composition according to any one of claims 1 to 4, characterized in that: Also contains antioxidants.

9. The thermoplastic resin composition according to any one of claims 1 to 4, characterized in that: Also contains light stabilizer.

10. The thermoplastic resin composition according to any one of claims 1 to 4, characterized in that The molded article of the thermoplastic resin composition has a hardness of ASKERC 30 to 50 (SRIS 0101 standard, 23±2° C.) and a haze value (JIS K 7136:2000 standard) of 15% or less. 11 . A cushioning member comprising a molded article of the thermoplastic resin composition according to claim 1 .

12. The buffer component according to claim 11, characterized in that: The cushioning component is for shoes. 13 . A composition for a 3D printer, comprising the thermoplastic resin composition according to claim 1 .

Citation Information

Patent Citations

  • Method of producing resin-molded transformer coil

    JP1984066110A